Main Ways of Development of the Tourism Potential of the Republic of Uzbekistan - Askarovich, Ulashev Khubbim (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides an overview of the tourist region, the stages of tourism development in Uzbekistan.